iTRAQ-based comparative proteome analyses of different growth stages revealing the regulatory role of reactive oxygen species in the fruiting body development of Ophiocordyceps sinensis - Tong,Xinxin; Wang,Fang; Zhang,Han; Bai,Jing; Dong,Qiang; Yue,Pan; Jiang,Xinyi; Li,Xinrui; Wang,Li; Guo,Jinlin (PeerJ, 2021)
In this study, using an isobaric tags for relative and absolute quantitation (iTRAQ ) approach coupled with LC-MS / MS and bioinformatics, the proteomes were analyzed for the crucial three stages covering the fruiting body development of Ophiocordyceps sinensis, including sclerotium (ST), primordium (PR) and mature fruiting body (MF), with a focus on fruiting body development-related proteins and the potential mechanisms of the development. A total of 1,875 proteins were identified. Principal Component Analysis (PCA) demonstrated that the protein patterns between PR and MF were more similar than ST. Differentially accumulated proteins (DAPs) analysis showed that there were 510, 173 and 514 DAPs in the comparisons of ST vs. PR, PR vs. MF and ST vs. MF, respectively. A total of 62 shared DAPs were identified and primarily enriched in proteins related to ‘carbon transport and mechanism’, ‘the response to oxidative stress’, ‘antioxidative activity’ and ‘translation’. KEGG and GO databases showed that the DAPs were enriched in terms of ‘primary metabolisms (amino acid/fatty acid/energy metabolism)’, ‘the response to oxidative stress’ and ‘peroxidase’. Furthermore, 34 DAPs involved in reactive oxygen species (ROS) metabolism were identified and clustered across the three stages using hierarchical clustering implemented in hCluster R package . It was suggested that their roles and the underlying mechanisms may be stage-specific. ROS may play a role in fungal pathogenicity in ST, the fruit-body initiation in PR, sexual reproduction and highland adaptation in MF. Crucial ROS-related proteins were identified, such as superoxide dismutase (SOD, T5A6F1), Nor-1 (T5AFX3), electron transport protein (T5AHD1), histidine phosphotransferase (HPt, T5A9Z5) and Glutathione peroxidase (T5A9V1). Besides, the accumulation of ROS at the three stages were assayed using 2,7-dichlorofuorescin diacetate (DCFH-DA) stanning. A much stronger ROS accumulation was detected at the stage MF, compared to the stages of PR and ST. Sections of ST and fruit-body part of MF were stained by DCFH-DA and observed under the fluorescencemicroscope, showing ROS was distributed within the conidiospore and ascus. Besides, SOD activity increased across the three stages, while CAT activity has a strong increasement in MF compared to the stages of ST and PR. It was suggested that ROS may act in gradient-dependent manner to regulate the fruiting body development. The coding region sequences of six DAPs were analyzed at mRNA level by quantitative real-time PCR (qRT-PCR). The results support the result of DAPs analysis and the proteome sequencing data. Our findings offer the perspective of proteome to understand the biology of fruiting body development and highland adaptation in O. sinensis, which would inform the big industry of this valuable fungus.
Keywords: Ophiocordyceps sinensis; Comparative proteome analyses; Fruiting bodydevelopment; Reactive oxygen species (ROS)